The Influence Of Togetherness And Solidarity On The Work Leadership Of Rt Apparatus In Belian Village, Batam Kota District Through The Spirit Of Mutual Cooperation - Anwar, Nur Effendi; Mulyadi , Andi; Mursal (CV ODIS, 2025)
The purpose of this study is to see the relationship and test the influence of togetherness and solidarity on the spirit of mutual cooperation, as well as to see the influence of togetherness and solidarity on the leadership of RT apparatus in Belian sub-district. Methodology: In this study, there are several stages that are carried out to get the expected results. Starting from conducting field observations, looking for what relationships can strengthen the spirit of mutual cooperation and improve the leadership of RT apparatus. Results: The results obtained from this study are that there is a strong influence between the variables studied due to the results obtained, namely the value of CR is greater than the value of the t-table, which shows that there is an influential effect on the research conducted. The relationship and influence between independent variables and dependent variables is quite strong and it can also be seen that the influence of the intervening variable The influence of Togetherness on Leadership Through the Spirit of Mutual Cooperation has a direct effect with the t-count value (1.882503) greater than the t-table (1.655), and this can be said that the relationship between the independent variable and the dependent variable and by using the intervening variable turns out to have a direct and significant influence result. Limitations: In this study, the researcher has limitations on the variables that are studied and this allows other researchers to use this research as a reference and replace some variables that are considered very influential to improve the leadership of the RT device.